Factors that Impede the Application of CLT in Afghan Public Universities: A Conceptual Review - Rahimi, Mahmood; Rahimi, Fahim (Modality Journal: International Journal of Linguistics and Literature, 2025)
This conceptual paper examines the factors that impede the application of Communicative Language Teaching (CLT) in English departments within Afghan Public Universities. Specifically, it explores the views of English as a foreign language (EFL) instructor’s, students and the challenges they face in the application of CLT in EFL classrooms. Through a comprehensive review of the existing literature and research findings, this study identified issues related to teachers and students, lack of resources and infrastructure, sociocultural issues, system-related, and language proficiency that hinders the application of CLT in the Afghan EFL higher education context. The findings suggest a critical need to address the challenges of boosting language education in Afghan higher education. By addressing and overcoming these challenges, educators and policymakers can improve the application of CLT, thereby enhancing the proficiency and communicative competence of EFL learners in Afghanistan.